Antiviral Potential Analysis of Jamblang Seed Essential Oil (Syzygium cumini) Using GCMS - -, Winarsih; Diningrat, Diky Setya; Sari, Ayu Nirmala; Harahap, Novita Sari; -, Kusdianti (Kalwedo Sains (KASA), 2021)
Jamblang (Syzygium cumini) essential oil is another form of extraction to explore its potential medicinal properties. This study aims to determine the content of bioactive compounds contained in seed essential oil using the Gas Chromatography Mass Spectophotometer (GCMS) approach. Jamblang seed essential oil is produced through a steam distillation process. The results of the GCMS analysis were evaluated using the MASSLAB program. The data obtained from the GCMS tool was then further analyzed using the PubChem NCBI database software (https://pubchem.ncbi.nlm.nih.gov/) and PASS online. The results of this study indicate that there are 61 phytochemical compounds in jamblang seed essential oil. Of the total bioactive compounds, there are 2 phytochemical compounds that are useful as antivirals, while those that have similarities above 80% are 10 compounds. The results of this study can be used as a basis for a program to develop the potential use of bioactive compounds in jamblang seed essential oil as an antiviral. In future research, it is necessary to analyze other plant parts and make comparisons to complete the existing database.